Benthic and planktonic stable isotopes of sediment core M94-481 PC - Dirk Nürnberg (PANGAEA, 2022)
Proxy parameter of core M94-481 PC: Benthic and planktonic stable isotopes of sediment core M94-481 PC. Isotope analyses were performed on the planktonic and benthic foraminiferal species Globigerinoides ruber (white), Globorotalia truncatulinoides, and Uvigerina peregrina, respectively. Sedimentological and logging data as well as the foraminiferal analyses were performed on piston core M94-481 PC, which was recovered from the northern Campeche Bank (Gulf of Mexico; 23°39.997 extquotesingleN 87°07.284 extquotesingleW) from 521 m water depth during R/V Meteor Cruise M94 in 2013 (https://doi.org/10.2312/cr_m94). Sampling and analytical studies were carried out from ~1.0 cm to 250.5 cm core depth at 1-3 cm spatial resolution. The records cover the last ~447 kyrs. The stable carbon (δ13C; extperthousand VPDB) and oxygen isotope (δ18O, extperthousand VPDB) analyses were performed on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV Carbonate Preparation Device. The isotope data provide stratigraphical information.